Zinc overload in weaned pigs: tissue accumulation, pathology, and growth impacts. (July 2019) - Burrough, Eric R.; De Mille, Carson; Gabler, Nicholas K.
Zinc oxide (ZnO) is commonly fed to pigs at pharmacologic concentrations (2, 000–3, 000 ppm) for the first 3 wk post-weaning to increase growth and reduce enteric bacterial disease. The safety of this high-dose treatment is assumed based upon lower bioavailability of ZnO compared to other common forms of Zn in feed; however, limited data are available regarding the specific serum and tissue concentrations of Zn expected in animals experiencing overload following feeding of excessive ZnO. Fifty-five 3-wk-old pigs were divided into 5 groups receiving various concentrations of ZnO (0–6, 000 ppm) for 3 wk. Pigs receiving 6, 000 ppm ZnO had higher mean pancreatic Zn concentrations ( p < 0.001) compared to other treatments, and higher pancreatic Zn concentrations were associated with pancreatic acinar cell apoptosis ( p < 0.0001). Hepatic Zn concentrations were highest for pigs receiving 6, 000 ppm ZnO (mean ± SEM; 729 ± 264 ppm) and significantly higher than all other groups ( p < 0.0001), with controls having concentrations <60 ppm. Similarly, serum Zn was highest in pigs receiving 6, 000 ppm ZnO (4.81 ± 2.31 ppm) and significantly higher than all groups (controls, <1 ppm). Additionally, as pigs became overloaded with Zn, there were significant reductions in serum Cu and both serum and hepatic Se. Hepatic and serum Zn concentrations >500 ppm and >2 ppm, respectively, are indicative of Zn overload, and dietary trace mineral analysis is warranted if expected inclusion rates are ≤3, 000 ppm ZnO.